(untitled) (Al-Qamar, 2020)
Islam is a natural religion which deals with all the aspects of human life, whether individual or social. Islam emphasis on the bringing up girls which was not allowed in Arabian society, before Islam. Prophet Muhammad (SAW) promised the one who brings up his daughters properly that he would be very close to him in Jannah. Islam terminated the discrimination between sons and daughters in various ways and ensured the rights of women whether as a mother, wife or daughter. But in the current age, women have been again denied their basic rights, including inheritance. There are several reasons behind this issue, which lead to deprivation of women from inheritance. Efforts have been made in this article to highlight these reasons. This article also deals with the religious, social and domestic issues regarding women’s inheritance. Efforts have also been made to suggest the ways to address these problems and to pave a way to the betterment of inheritance matters as laid down in the teaching of Quran and Sunnah.